2008
DOI: 10.1529/biophysj.107.126664
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Epitope Region of a Peptide from the Streptomyces coelicolor Phosphoenolpyruvate:Sugar Phosphotransferase System Able to Bind to the Enzyme I

Abstract: The bacterial PEP:sugar PTS consists of a cascade of several proteins involved in the uptake and phosphorylation of carbohydrates, and in signal transduction pathways. Its uniqueness in bacteria makes the PTS a target for new antibacterial drugs. These drugs can be obtained from peptides or protein fragments able to interfere with the first reaction of the protein cascade: the phosphorylation of the HPr by the first enzyme, the so-called enzyme EI. To that end, we designed a peptide, HPr(9-30), spanning residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
1
15
2
Order By: Relevance
“…6), unless we have experimental evidence, we cannot rule out fully this second explanation. Next, the higher value could be due to the presence of the self-association equilibrium involving the HPr bs ; for instance, we have observed that dimerization of the intact EI sc affects its binding to HPr sc [62]. And finally, we have shown that peptides [20], which do not mimic the natural target of EIN sc -HPr sc interface (instead, they were obtained by phage display and combinatorial techniques), bound stronger to EIN sc than peptides derived from PTS proteins of the same species.…”
Section: Discussionmentioning
confidence: 96%
“…6), unless we have experimental evidence, we cannot rule out fully this second explanation. Next, the higher value could be due to the presence of the self-association equilibrium involving the HPr bs ; for instance, we have observed that dimerization of the intact EI sc affects its binding to HPr sc [62]. And finally, we have shown that peptides [20], which do not mimic the natural target of EIN sc -HPr sc interface (instead, they were obtained by phage display and combinatorial techniques), bound stronger to EIN sc than peptides derived from PTS proteins of the same species.…”
Section: Discussionmentioning
confidence: 96%
“…We preferred using the isolated mutant peptides to study the effect of helicity on binding, instead of the entire mutated HPr, since we showed previously that the isolated wild-type peptide of HPr ( Table 3 ) had a similar affinity for EIN and Rsd to that of the intact HPr for the same proteins [ 24 , 28 , 31 ]. By using the designed peptides ( Table 1 ), we avoided any other possible interactions that could have the mutated residues with the rest of HPr.…”
Section: Methodsmentioning
confidence: 99%
“…We have carried out an extensive description of the structures and conformational stabilities of HPr sc (O50515) and EI (EI sc ) (Q9KZP1) to understand their binding in the PTS cascade [ 11 , 12 , 26 , 27 ]. We have also characterized the interaction of EI sc with wild-type HPr sc [ 28 ] and that of the phosphorylated species [ 29 ], as well as that of the N-terminal domain of EI sc (EIN sc ) with intact HPr sc [ 10 , 29 ]. We have also shown that the peptide comprising residues Ala9-Gly30 of HPr sc (HPr 9–30 ) is mainly disordered in aqueous solution (with about 7% of helical population) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, we identified more than 500 articles after searching Web of Science, PubMed, SciDir and OVID databases using ‘isothermal AND titration AND calorimetry’ or ITC or ‘Isothermal Titration Calorimetry’ search terms. Following the format of previous annual surveys these have been classified into the following categories: References cited in the text and review articles 1–82. Protein–protein and protein–peptide interactions 83–222. Protein–small ligand or protein–drug interactions 223–321. Protein/peptide metal interactions 322–355. Protein/peptide nucleic acid interactions 356–387. Protein/peptide lipid interactions …”
Section: Introductionmentioning
confidence: 99%